2021
DOI: 10.1016/s1473-3099(20)30914-2
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker-guided tuberculosis preventive therapy (CORTIS): a randomised controlled trial

Abstract: Summary Background Targeted preventive therapy for individuals at highest risk of incident tuberculosis might impact the epidemic by interrupting transmission. We tested performance of a transcriptomic signature of tuberculosis (RISK11) and efficacy of signature-guided preventive therapy in parallel, using a hybrid three-group study design. Methods Adult volunteers aged 18–59 years were recruited at five geographically distinct communities in South Africa. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
109
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 21 publications
2
109
0
1
Order By: Relevance
“…padj, adjusted P value. CORTIS; NCT02735590), which concluded that a reduced signature RISK11 derived from the Zak 16-gene signature (Zak et al, 2016) was better suited to screening of symptomatic individuals with possible early clinical TB than for mass community-based screening for incipient TB (Scriba et al, 2021). It is unclear whether this signature can distinguish subclinical or active TB from other infections, particularly viral infections, which may present with symptoms similar to clinical TB and are also dominated by type I IFN signaling (Singhania et al, 2018a;Singhania et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…padj, adjusted P value. CORTIS; NCT02735590), which concluded that a reduced signature RISK11 derived from the Zak 16-gene signature (Zak et al, 2016) was better suited to screening of symptomatic individuals with possible early clinical TB than for mass community-based screening for incipient TB (Scriba et al, 2021). It is unclear whether this signature can distinguish subclinical or active TB from other infections, particularly viral infections, which may present with symptoms similar to clinical TB and are also dominated by type I IFN signaling (Singhania et al, 2018a;Singhania et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…Existing TB diagnostic tools are limited in their scope and dependent on sputum availability for rapid identification of TB. Diagnostic blood transcriptomic signatures of TB may provide a pathway to support early diagnosis for a broader spectrum of disease phenotypes, although there is little consensus between reported reduced signatures for TB risk and those that distinguish active TB from LTBI ( Kaforou et al, 2013 ; Maertzdorf et al, 2016 ; Penn-Nicholson et al, 2020 ; Roe et al, 2016 ; Scriba et al, 2021 ; Singhania et al, 2018a ; Singhania et al, 2018b ; Suliman et al, 2018 ; Sweeney et al, 2016 ; Zak et al, 2016 ). Moreover, there is a need to distinguish TB from other confounding diseases ( Kaforou et al, 2013 ; Singhania et al, 2018a ; Singhania et al, 2018b ).…”
Section: Discussionmentioning
confidence: 99%
“…The infection diagnostic tests (TST and IGRAs) are positive and remain positive in subsequent stages towards TB disease. In future, new biomarkers will enable the specific diagnosis of incipient TB that is going to progress to subclinical or clinical TB, possibly by identifying host ribonucleic acid (RNA) signatures [26][27][28]. Larger studies are needed to confirm the accuracy of these results.…”
Section: Incipient Tbmentioning
confidence: 99%
“…In such populations, microbiological tests are not always feasible due to the limited ability to produce good quality sputum samples or due to low bacterial loads in their samples. In the future, it will be of interest (i) to evaluate if RISK6 is able to predict the risk of progression to TB as demonstrated by the RISK11 signature 25 and (ii) to assess the diagnostic performance of RISK6 signature as a prototype cartridge assay as it has already been evaluated for the 3-gene signature against a microbiological reference standard 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is much active research 23 , 24 on human blood transcriptomic TB biomarkers 25 . A six whole blood gene transcriptomic signature (RISK6) has been recently described and validated in 7 independent cohorts, demonstrating its utility to predict the risk of progression from TB infection to ATB disease, as a screening test for TB, and to monitor TB treatment response 19 , 26 .…”
Section: Introductionmentioning
confidence: 99%